Knowledge and Compliance with a Hypertension Diet Among Elderly Patients - Astuti, Vina; Supratman, Supratman (Jurnal Keperawatan Profesional (KEPO), 2025)
Hypertension remains a global health concern, with high prevalence rates in Indonesia, particularly among the elderly aged 60 and above. The high incidence of hypertension in Pajang, Surakarta, is believed to stem from limited awareness regarding the importance of a hypertension diet as a non-pharmacological treatment. This study is a quantitative study with a correlational design. The sample consisted of 100 elderly subjects with hypertension in the working area of the Pajang Community Health Center, selected using simple random sampling. This study was conducted in 2025. As the data were not normally distributed, the Spearman rank correlation test was used for analysis. The findings showed that 79% of subjects had good knowledge, and 82% demonstrated good dietary compliance. A strong positive correlation was found between knowledge and compliance (r = 0,589, p-value <0,001), confirming a significant relationship between the two among elderly patients in the Pajang Community Health Center, Surakarta. Elderly patients was encouraged to continue enhancing their understanding of dietary management for hypertension, whether through health professionals or reliable information sources. With greater knowledge, patients are expected to be more consistent in maintaining a healthy diet, which in turn can help control blood pressure and prevent complications.